Essential waters: Young bull sharks in Fiji's largest riverine system. Issue 13 (13th June 2019) - Glaus, Kerstin B. J.; Brunnschweiler, Juerg M.; Piovano, Susanna; Mescam, Gauthier; Genter, Franziska; Fluekiger, Pascal; Rico, Ciro
Abstract: Coastal and estuarine systems provide critical shark habitats due to their relatively high productivity and shallow, protected waters. The young (neonates, young‐of‐the‐year, and juveniles) of many coastal shark species occupy a diverse range of habitats and areas where they experience environmental variability, including acute and seasonal shifts in local salinities and temperatures. Although the location and functioning of essential shark habitats has been a focus in recent shark research, there is a paucity of data from the South Pacific. In this study, we document the temporal and spatial distribution, age class composition, and environmental parameters of young bull sharks ( Carcharhinus leucas ) in the Rewa, Sigatoka, and Navua Rivers, Fiji's three largest riverine systems. One hundred and seventy‐two young bull sharks were captured in fisheries‐independent surveys from January 2016 to April 2018. The vast majority of the captures were neonates. Seasonality in patterns of occurrence of neonate individuals suggests a defined parturition period during summer. Environmental parameters between the Rewa and the Sigatoka River differed significantly, as did the recorded young bull sharks abundance. According to the surveys, young bull sharks occur in all three rivers with the Rewa River likely representing essential habitat for newly born bull sharks. These results enhance the understanding of bull shark ecology in Fiji and provide a scientific basis for the implementation of local conservation strategies that contribute to the protection of critical habitats. Abstract : We report a field‐based study which assessed juvenile bull shark abundance across the major rivers of Viti Levu, Fiji, a shark data deficient region of the world. We discovered that the Rewa River is likely to be an essential habitat for neonate bull sharks and might be used for parturition, and subsequently as a nursery ground. Our manuscript also highlights that within the Rewa River neonate bull sharks occurred in lower than previously reported salinity conditions.